Análisis de técnicas de recuperación antigénica para la detección inmunohistoquímica del virus de la diarrea viral bovina - Marini, M.R. (2006)
In the present work different methods of antigen retrieval were evaluated to allow the immunodetection of the Bovine Viral Diarrhea virus (BVDv) in materials fixed with formol. The effect of the application of proteolytic digestion was analyzed (ficin, trypsin, pepsin, proteinase K) and its combination with treatment in a microwave oven using different concentrations and times of incubation for the primary antibody. The most effective treatment was the one carried out with proteinase K, using 1:30 dilution for the primary antibodies, with overnight incubation at room temperature. We conclude that the formol fixation affects the antigenicity of the BVDv but these effects can be reverted by specific proteolytic digestion allowing the use of the immunohistochemical routine technique for the diagnosis of the disease.